Hydrogeochemical and geothermal controls on the formation of high fluoride groundwater - Wang, Zhen; Guo, Huaming; Xing, Shiping; Liu, Haiyan (Journal of hydrology (Amsterdam), 2021)
•Natural high-F– groundwater mainly occurs in confined aquifers in the Guide basin.•Along the flow path, F– is gradually enriched in groundwater in confined aquifer.•High-F– groundwater is characterized by low Ca2+ and high Na+, pH, HCO3–•Precipitation of Ca2+ enhances dissolution of F–-bearing minerals and release of F–•Geothermal waters favor F– enrichment in confined groundwater. High fluoride (F–) concentrations in groundwater affected by geothermal activity have been reported worldwide, but the genesis mechanism is not adequately understood. In this study, 92 groundwater samples and 63 sediment samples were collected from the China’s Guide basin for chemical analyses and laboratory tests. Results indicate that groundwater F– concentrations continuously increase along a flow path, being consistent with trends of Na+ and HCO3– concentrations, Na/Ca molar ratio, and pH values, while Ca2+ concentrations show a decreasing trend. Water-soluble F– contents in sediments increase as the depth increases. Higher-F– groundwater samples generally have lower δD and δ18O values than those of lower F– samples. The major hydrogeochemical processes controlling the formation of high-F– groundwater include precipitation of Ca2+ or cation exchange between Ca2+ and Na+ or both, which enhance dissolutions of F–-containing minerals and facilitate the release of F– into groundwater. Slightly alkaline environments and increased HCO3– and CO32– concentrations favor desorption of F– from solid surfaces into groundwater. Closed hydrogeological conditions and long-term water–rock interactions in confined aquifers accumulate F– in groundwater. Exposed geothermal springs around the Guide basin also contribute to the formation of high-F– groundwaters directly by the input of geothermal water and indirectly by heat transfer into aquifers at a regional scale, which is a problem deserving further investigation.